Overview of the infant and young child feeding policy environment in Pakistan: Federal, Sindh and Punjab context - Hana Mahmood; Yasmeen Suleman; Tabish Hazir; Durre Samin Akram; Shahadat Uddin; Michael J Dibley; Saleem Abassi; Amara Shakeel; Narjis Kazmi; Anne Marie Thow (BMC, 2017)
Abstract Background Appropriate infant and young child feeding (IYCF) practices have been identified as important for appropriate child growth and development. (Ministry of Planning and Development, Ministry of National Health Services, Regulations and Coordination (2012)) Children in Pakistan still experience high rates of malnutrition, indicating a likely need for stronger IYCF policy. The purpose of this study was to identify major stakeholders who shape the IYCF policy environment and analyze which policies protect, promote and support IYCF practices, either directly or indirectly. Methods This study was conducted at the federal level, and in the provinces of Sindh and Punjab. We identified policies relevant to IYCF using a matrix developed by the South Asian Infant Feeding Research Network (SAIFRN), designed to capture policies at a range of levels (strategic policy documents through to implementation guidelines) in sectors relevant to IYCF. We analyzed the content using predetermined themes focused on support for mothers, and used narrative synthesis to present our findings. For the stakeholder analysis, we conducted four Net-Map activities with 49 interviewees using the Net-Map methodology. We analyzed the quantitative data using Organizational Risk Analyzer ORA and used the qualitative data to elucidate further information regarding relationships between stakeholders. Results We identified 19 policy documents for analysis. Eleven of these were nutrition and/or IYCF focused and eight were broader policies with IYCF as a component. The majority lacked detail relevant to implementation, particularly in terms of: ownership of the policies by a specific government body; sustainability of programs/strategies (most are donor funded), multi-sectoral collaboration; and effective advocacy and behavior change communication. Data collected through four Net-Map activities showed that after devolution of health ministry, provincial health departments were the key actors in the government whereas UNICEF and WHO were the key donors who were also highly influential and supportive of the objective. Conclusion This analysis identified opportunities to strengthen IYCF policy in Pakistan through increased clarity on roles and responsibilities, improved multisectoral collaboration, and strong and consistent training guidelines and schedules for community health workers. The current policy environment presents opportunities, despite limitations. Our Net-Map analysis indicated several key government and international stakeholders, who differed across Federal and Provincial study sites. The detailed information regarding stakeholder influence can be used to strengthen advocacy.